Capital Structure and Firm’s Profitability: Evidence From Listed Consumer Goods Sector in Nigeria - P. I., Udobi-Owoloja; M.A., Gbajumo-Sheriff; B., Umoru; S.A, Babatunde; D, Ilimezekhe (Journal of Accounting, Business and Finance Research, 2020)
This study investigated the impact of capital structure on profitability of consumer goods firms in Nigerian for a period of eight years (2011-2018). Data of ten (10) randomly selected listed firms of the Nigeria Stock Exchange were derived from the firms’ published financial reports for the period covered. The panel regression results revealed that Debt to Asset Ratio(DAR) is positively significant on Return On Asset(ROA) (Proxy for profitability),while other proxies of capital structure shows that Debt to Equity(DER), Liquidity Ratio(LIQ), are not statistically significant, Short Term Debt to Total Asset Ratio (SDTA) shows a negative connection, Firm Size (FS) has a weak correlation with profit and Long Term Debt to Total Asset Ratio (LDTA) do not influence firms’ profitability of the consumer goods sector of Nigeria economy. In conclusion, capital structure influences the profitability of consumer goods sector of Nigerian Stock Exchange. It was recommended that firms in that sector should leverage on debt financing to boost their earnings as interest payment on debt is tax deductible.